Czech political candidate and donation datasets - Linek, Lukáš; Škvrňák, Michael; Šoltés, Michal; Titl, Vítězslav (Scientific data, 2025)
This paper introduces a new Czech Political Candidate Dataset (CPCD), which compiles comprehensive data on all candidates who have run in any municipal, regional, national, and/or European Parliament election in the Czech Republic since 1993. For each candidate, the CPCD includes their first name, last name, age, gender, place of residence, university degree, party membership, party affiliation, ballot position, and election results for candidates and for parties. We match candidates over various elections by using algorithms that rely on their personal information. We add information on political donations made to political parties. We source donation information from the Czech Political Donation Dataset (CPDD), our other newly built dataset, in which we compile records of individual donations to 12 leading political parties from official records for the period from 2017 to 2023. CPDD is publicly available along with the CPCD.
Keywords: Politics; politika; Humans; Česká republika; lidé; Czech Republic